TINJAUAN KONDISI SOSIAL EKONOMI PENARIK BECAK DI KELURAHAN BANTAN KECAMATAN MEDAN TEMBUNG DI MASA COVID-19 - Sania Wulandari; Agus Suriadi (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2022)
During a pandemic, it results in reduced community activity. One of the sectors that is currently the government's attention is the informal labor sector. From an economic perspective, most of the people of Bantan Village, Kec. Medan Tembung has heterogeneous livelihoods, namely working as a rickshaw puller. This situation certainly affects the income of motorized rickshaw drivers, especially motorized rickshaw drivers. Convex Field. Many of these motorbike rickshaw drivers now feel that their socio-economic life is in a deteriorating state. The life of the surviving rickshaw drivers is quite alarming. More and more competitors automatically make their income decrease. Not to mention that the price of basic necessities is getting more expensive, and the Covid-19 pandemic is making their lives even more difficult. So that this affects their social conditions such as getting bad behavior from people around them, but some rickshaw pullers also help each other during this covid-19 pandemic This study aims to determine the socio-economic conditions of the Becak Puller in Bantan Village, kec. Tembung fields during the Covid-19 period. The research method used is descriptive qualitative to get a clear picture of the socio-economic conditions of rickshaw drivers. Sampling using accidental sampling by collecting data through observation and interviews. Based on research that has been carried out, the results of the study show that the socio-economic life of motorized pedicab drivers during the Covid-19 pandemic in the Kel. Bantan Kec. Medan Tembung is decreasing and is still classified as a low-income community. This is evidenced by the income generated by the informants and the need to get a side job to meet the daily needs of their family, including to pay for children's education. During the Covid-19 pandemic, motorized rickshaw drivers lost their income and looked for ways to survive in a situation like this, by reducing expenses, asking for family assistance and making loans